Technique and impact on first pass effect primary results of the ASSIST global registry - Gupta, Rishi; Miralbés, Salvador; Bonilla, Angel Calleja; Naravetla, Bharath; Majjhoo, Aniel Q.; Rayes, Mahmoud; Spiotta, Alejandro M.; Loehr, Christian; Cioltan, Andreea; Vollherbst, Dominik; Martínez-Galdámez, Mario; Galván-Fernandez, Jorge; et al. (Journal of neuroInterventional surgery, 2024)
Background Patients treated with mechanical thrombectomy (MT) for acute ischemic strokes from large vessel occlusion (LVO) have better outcomes with effective reperfusion. However, it is unknown which technique leads to better technical and clinical success. We aimed to determine which technique yields the most effective first pass reperfusion during MT. - Methods In a prospective, multicenter global registry we enrolled patients treated with operator preferred MT technique at 71 hospitals from January 2019 to January 2022. Three techniques were assessed: SR Classic with stent retriever (SR) and balloon guide catheter (BGC); SR Combination which employed SR with contact aspiration with or without BGC; and direct aspiration (DA) with or without BGC. The primary outcome was achieving an expanded Thrombolysis In Cerebral Infarction (eTICI) score of 2c or 3 on the first pass, with the primary technique as adjudicated by core lab. The primary clinical outcome measure was a 90-day modified Rankin Scale (mRS) score of 0-2. - Results A total of 1492 patients were enrolled. Patients treated with SR Classic or SR Combination were more likely to achieve first pass eTICI 2c or 3 reperfusion (P=0.01). There was no significant difference in mRS 0-2 (P=0.46) or safety endpoints. - Conclusions The use of SR Classic or SR Combination was more likely to achieve first pass eTICI 2c or 3 reperfusion. There were no significant differences in clinical outcomes and safety endpoints.